POWER2GAS IN GERMANY – TECHNOLOGY AND OPPORTUNITIES - Hansen, Lisa Christin; Bojahr, Philipp; Timmerberg, Josef (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
For the future, Germany banks on renewable energy. That bears a challenge, because this energy generation heavily depends on climate conditions. Therefore, a proper storage technology is needed to ensure the energy supply all over the year. Furthermore, the expansion of renewable power plants and the power grid expansion advance in different pace. The power grid operators have to react with feed-in management actions to safe the grid against overloading. As a consequence, operators have to switch off some of their windmills if the wind blows to strong. Suitable storage technologies will help to avoid shutting down renewable power plants to generate the full energy potential. A promising technology is Power2Gas. These facilities transform electrical energy into gas, which could be stored in the huge German gas network.